Pengaplikasian manajemen strategi pada bank konvensional di Indonesia - Indinanta, Anisa; Rosida, Alfiyah Fajar; Nurjihan, Mumtazah (Maliki Interdisciplinary Journal, 2023)
A strategic plan is a very important point in the sustainability of an organization or company. In the financial sector such as banks, strategic plans are also very necessary to maintain and become competitive with other competitors. This research aims to analyze and compare the strategic plans of Allo Bank Indonesia, BCA, and Bank Bukopin in a conventional context.